The welfare impact of traditional taming on Asian elephant (Elephas maximus) calves in Myanmar: Assessing the influence of personality - Newman, Lucy (2024)
Asian elephants (Elephas maximus) have experienced a global population decline of at least 50% over the last 75 years, due to various anthropogenic activities. As wild numbers decrease, there is greater dependence on (semi-)captive populations, particularly in range countries, to preserve this endangered species. Currently, ~30% of the remaining ~50,000 Asian elephants live in captivity, a proportion expected to rise in future. However, captive populations are also in decline, due partially to high calf mortality. Elephants in captivity rely on human management, and so keepers/handlers have a responsibility to maintain good health and welfare of all individuals. Welfare refers to an animal’s collective physical, mental, and emotional states over time. Poor welfare is associated with reduced reproduction, and increased morbidity and mortality, which all limit population growth.